Reduction of monsoon rainfall in response to past and future land use and land cover changes (2016)
Land use and land cover changes (LULCC) can have significant biophysical impacts on regional precipitation, including monsoon rainfall. Using global simulations with and without LULCC from five general circulation models, under the Representative Concentration Pathway 8.5 scenario, we find that future LULCC significantly reduce monsoon precipitation in at least four (out of eight) monsoon regions. While monsoon rainfalls are likely to intensify under future global warming, we estimate that biophysical effects of LULCC substantially weaken future projections of monsoons' rainfall by 9% (Indian region), 12% (East Asian), 32% (South African), and 41% (North African), with an average of ~?30% for projections across the global monsoon region. A similar strong contribution is found for biophysical effects of past LULCC to monsoon rainfall changes since the preindustrial period. Rather than remote effects, local land?atmosphere interactions, implying a decrease in evapotranspiration, soil moisture, and clouds along with more anticyclonic conditions, could explain this reduction in monsoon rainfall.